Seed micromorphological study on endemic and subendemic species of Veronica L. (Plantaginaceae Juss.) in Iran (Bangladesh Journal of Plant Taxonomy, 2019)
Seed morphology of 12 Iranian endemic and subendemic species of Veronica was studied using scanning electron microscope (SEM). Seven qualitative and quantitative characters were measured using SEM micrographs and stereomicroscopy. The seed shape of most species is ovate and plano-convex. The size of seeds ranges from 1.25 x 0.75 mm in V. khorassanica to 2.5 x 1.75 mm in V. viscosa Boiss. The ornamentation of seed coat is reticulate-verrucate in V. khorassanica, V. czerniakowskiana, V. mazanderanae and V. rubrifolia, reticulate-rugate in V. acrotheca, V. aucheri, V. viscosa and V. intercedens, rugose in V. microcarpa, V. chionantha and V. rechingeri, and reticulate-porate in V. gaubae. The testa cells are polygonal in ten species and irregular in two species. Micromorphological characters of seeds are useful in specific and subspecific delimitations of Iranian Veronica.